Peran Penyuluhan Sebagai Upaya Peningkatan Kesadaran Masyarakat Terhadap Perlindungan Perempuan Dan Anak Di Desa Masebewa - Yoseph Darius Purnama Rangga; Gervasius Febriano Valentino Judi; Lusia Rosita Lango; Maria SIsilia Virly Radja; Julianto Edwar Baber; Alfonsia Putri Getan; Maria Afrilanti Dua Kasan (JPMNT JURNAL PENGABDIAN MASYARAKAT NIAN TANA, 2025)
The 2025 Nusa Nipa University Community Service Program (KKN) in Masebewa Village aims to raise public awareness of the protection of women and children through outreach, given the increasing number of cases of physical, sexual, and psychological violence that are often resolved within the family without reporting. The methods used included discussion sessions and the delivery of educational materials on legal basis (such as Law No. 23 of 2004), women's and children's rights, forms of violence, and solutions. The program was implemented over two weeks (July 14-26, 2025) in each neighborhood unit (RT), neighborhood unit (RW), parents, housewives, teenagers, youth, and children through a participatory approach.The results of the program demonstrated active community participation, increased understanding, increased courage for victims to speak out, and collective awareness for preventing and reporting violence, thus creating a safer and more caring environment in Masebewa Village.